Evaluation of different heat treatments applied to UHT milk added with transglutaminase - SILVA, Ramon Altivo Domiciano da; Francisquini, Júlia; Alves, Natália Maria Germano; Oliveira, Elisa Reis Silva de; Carvalho, Marcos Filgueiras Casadio; Perrone, Italo; Stephani, Rodrigo (Food Science and Technology, 2025)
Milk is a nutritionally rich food, seen as a source of essential macronutrients and micronutrients. Lactose, which is milk’s main carbohydrate, can be poorly metabolized by intolerant individuals, and it has led to the production of milk types with hydrolyzed lactose because they are more susceptible to non-enzymatic browning (Maillard reaction). Milk is subjected to heat treatments for preservation purposes, but it can cause undesirable changes in it. Strategies such as using stabilizing salts and transglutaminase have been explored as ways to minimize these effects. This enzyme catalyzes isopeptide bonds and improves milk technological quality. The aim of the present study was to investigate physicochemical and colorimetric parameters in whole milk, in whole milk added with transglutaminase, in lactose-free whole milk, and in lactose-free whole milk added with transglutaminase treated under different thermal conditions. Results have shown that refrigeration had a significant impact on hydrogen potential, ionic calcium, and particle size. In addition, transglutaminase addition increased thermal coagulation time in zero-lactose whole milk. Enzyme transglutaminase increased the browning index in most whole milk samples and reduced it in zero-lactose whole milk. Finally, this enzyme was able to reduce particle size.